High-precision two-dimensional angle sensor using a dot array of a diffractive optical element. (6th July 2021) - Kim, Jong-Ahn; Lee, Jae Yong; Kang, Chu-Shik; Woo, Jae Heun
Abstract: An angle sensor is developed for measuring two-dimensional (2D) angular displacement. A periodic 2D dot array was generated using a diffractive optical element, and the 2D incident angle of the collimated incident beam was obtained by detecting the multiple peak positions of the 2D dot array. This strategy can reduce random error and periodic nonlinearity effects effectively, and achieve higher precision comparing with a conventional autocollimation principle. Stability of readout of a prototype sensor was evaluated as less than 0.000 3″ with averaging time of 8 s. When 2D angular displacements over ±100″ were simultaneously measured by the prototype sensor and a commercial autocollimator, the maximum deviation was less than 0.11″.